Prospek dan Strategi Pengembangan Jagung (Zea Mays L) Berbasis Agribisnis di Kota Parepare - Jaya, J; Zulkifli, Z; Nurhapsa, N. (Journal Galung Tropika, 2020)
The food crop sub-sector has an important and strategic role in national development. The development of the agribusiness sector in Indonesia as an integral part of national development has a very strategic role in the recovery of the national economy. The role of the food crop sub-sector not only to food security but also contributes substantially to the increase of Gross Domestic Product, the provision of food, the provision of industrial raw materials, the increase of exports and foreign exchange, poverty alleviation, the provision of employment opportunities, the source of farmer’s income and welfare Communities, and regional and national economies. This study aims: 1) To analyze the prospect of agribusiness system in corn commodity development in Parepare City which includes upstream agribusiness sub-system, Agricultural Business sub-system and downstream agribusiness sub-system; 2) To examine the policy strategy that can support the implementation of agribusiness system of corn commodity in Parepare City. Location of research in Kecamatan Bacukiki Kota Parepare, Technic of data analysis used is qualitative discriptive analysis and SWOT Analysis. The results showed that. L) the application of agribusiness system in corn commodity development in general is not maximal, 2) policy strategy that can support corn commodity development with agribusiness approach are: (a) optimize land utilization and improve performance of extension officer in development of corn farming, (b) Human resources development through training of both farmers and officers. (C) enhancing government support through agribusiness-based project activities (d) establishing partnerships with agribusiness actors or entrepreneurs; (e) enhancing the role of banks and other financial institutions in strengthening farmers’ capital and streamlining existing institutional presence within Support the corn agribusiness development program, (f) streamline marketing channels both production and production facilities.